METODE RELAKSASI NEWTON DAN KELAKUAN DINAMIKNYA - Yuniza '; Leli Deswita; Asmara Karma (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
We discuss a relaxation of Newton method, obtained by introducing a functioncomposed of the original function in an existing problem and its derivative. This methods consists of two parameters. Certain values of the parameters give several known iterative methods. Using Taylor expansion, we show that the method is of order two. We compare the relaxation of Newton method with other known existing methods using some test functions by looking at the number of the methods obtaining the roots of the problem and using Basins of Attraction.